THE LANGUAGE CRISIS OF NINETEENTH CENTURY AND PERSPECTIVE OF LAKSHMINATH BEZBARUAH - Yesmin, Gultaz (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Lakshminath Bezbaruah (1868-1938) is a memorable name in the field of Assamese language, literature and culture. He was a poet, story writer, novelist, dramatist, lyricist, essayist, biographer, autobiographer, writer of humour, and folk culture. Although, Lakshminath Bezbaruah had lightened all the segments of Assamese Literature by his excellency, but his contribution to the field of short story writing is significant. Bezbaruah started writing short stories when Short story writing was not flourished properly in it’s birthplace, the western nations itself. A new era was also started with his dramas, specially by his contribution to the Historical plays. It is his immense love towards his birthplace and mother tongue, the knowledge attained while studying in Kolkata about the western literature and the influence of the Thakur family are the main source of inspiration for him to write. Bezbaruah tried to restructure the Assamese society which was becoming lazy due to lack of intelligence exercise and materialistic attitude. By literature, he tried to aware the people of Assam. Bezbaruah has provided the Assamese literature a different form by his unique literary technique. His contribution to Assamese literature is multi dimensional. His immense love to his native land, sense of nationalism, social obligations, secularism, human values are his chief ornaments. Overcoming the narrowness of Assamese life, he always tried to represent Assamese literature in the global scenery for which he can be recognised as the pathfinder of modern Assamese literature. Lakshminath Bezbaruah was significantly famous among the writers who tried to give a new form to Assamese literature and culture by their works. Lakshminath Bezbaruah was not directly associated with any of the Indian national movement. He tried to restructure the Assamese literature and culture by studying it. He observed that to become a free nation one should be rich in language, culture and literature. Lakshminath Bezbaruah was one of the topmost intellect of the last decades of the nineteenth and first half of the twentieth. His chief objective of life was development of Assamese language and literature. He profoundly believed that language is the ultimate way of developing his own land and culture. In his vision, Assamese is such a beautiful language that no one can find another language like it in the whole world. The conflicts faced by Assamese language can be seen from some of his works, essay, his debate with other intellectuals, his speech in his presidency of Assam Sahitya Sabha. This thesis paper doesn’t include and discuss all the corners for the limited range. In the limit this thesis paper is prepared selecting the subject named “The Language Crisis of Nineteenth Century and Perspective of Lakshminath Bezbaruah”. Lakhsminath Bezboruwa had taken a middle path in the deterioration of the Assamese language. In one hand he condemned the Bengali officers and other hand the high ranked British officials for the deterioration of Assamese language. In this regard Bezboruwa’s vision is different from his contemporary Hemchandra Gowswami, Padmanath Gohain boruwah.